Peranan Intelegensi dan Bakat dalam Pembelajaran - Jannatul Wardiyah (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2021)
Intelligence and talent are inborn potentials that are owned by each individual. This potential will then support the learning process of students. This study uses descriptive analysis method, which aims to examine the role of intelligence and talent in learning. The findings of this study are intelligence and talent affect the success of students' learning. The success of students' learning depends on their intelligence and talents. So it is not something strange if there is a difference in the level of speed of students in solving problems. Educators in conducting learning are advised to pay attention to the potential that exists in each student to achieve maximum learning outcomes..